1995
DOI: 10.1089/jop.1995.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Apraclonidine Protection of the Blood-Aqueous Barrier from Traumatic Break-Down

Abstract: This study investigated the effects of apraclonidine hydrochloride 1% eye drops on blood-aqueous barrier in 108 pigmented rabbits. The effects of pretreatment with dapiprazole and yohimbine, and a comparison with clonidine 0.125% eye drops are also reported. The disruption of blood-aqueous barrier was obtained by argon laser burning of the iris. The degree of permeability of the barrier was deduced by the amount of proteins in aqueous humor 60 min after laser application. Intraocular pressure and pupil diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Bonomi et al [14] reported that pretreatment with apraclonidine 1% eyedrops completely protected the blood-aqueous barrier from disruption caused by laser burning of the iris. Our findings using PGE 2 and clonidine were similar to the data using laser burning and apraclonidine reported by Bonomi et al [14]. Anti-inflammatory actions of clonidine have previously been reported by Holsapple et al [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonomi et al [14] reported that pretreatment with apraclonidine 1% eyedrops completely protected the blood-aqueous barrier from disruption caused by laser burning of the iris. Our findings using PGE 2 and clonidine were similar to the data using laser burning and apraclonidine reported by Bonomi et al [14]. Anti-inflammatory actions of clonidine have previously been reported by Holsapple et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of clonidine significantly reduced the acute inflammatory swelling of the rat paw produced by carrageenin, histamine and serotonin [12]. Topical apraclonidine (paminoclonidine) reduced the intraocular pressure rise and elevation of the aqueous humor protein following YAG and argon laser irradiation to the rabbit iris [13,14]. We have previously reported that transcorneal diffusion of prostaglandin E 2 (PGE 2 ) using a glass cylinder produced aqueous flare elevation in pigmented rabbits [15].…”
Section: Introductionmentioning
confidence: 99%
“…These features render the rat a potentially useful surrogate to study IOP control mechanisms and actions of antiglaucoma drugs. Several models use techniques that raise IOP by physically damaging ocular structures, such as laser destruction of the trabecular meshwork, or cauterization of episcleral veins [5,7,21]. Such models are useful, as the elevated IOP can be studied in the conscious state over time, although intermittent, indirect measurements of IOP are used.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine, however, causes cardiovascular effects after systemic absorption from the eye [1]. Apraclonidine (AP, p-aminoclonidine) is more commonly used topically for glaucoma, as it penetrates the cornea and blood-brain barrier to a lesser extent and, thus, has fewer adverse systemic effects [3][4][5]. AP is effective in animal models of elevated IOP as well as glaucoma in humans.…”
Section: Introductionmentioning
confidence: 99%